Association of Cutaneous Amyloidosis with Neurodegenerative Amyloidosis: Correlation or Coincidence? - Awal, Guneet (J Clin Aesthet Dermatol, 2018)
Neurodegenerative disorders such as Alzheimer’s disease and localized cutaneous macular amyloidosis are conditions that result from protein misfolding. These disorders share common pathogenic mechanisms that lead to the deposition of amyloid protein. Currently, there is a paucity of data on the connection between the brain and skin amyloidosis. Few recent studies have demonstrated a strong connection between the brain and skin in different amyloid diseases. Here, we report a case of concurrent occurrence of skin and brain amyloidoses and explore the brain-skin axis connection.